Metastatic epithelioid malignant peripheral nerve sheath tumor in a known case of neurofibromatosis-1, cytomorphological appearance, and critical analysis of immunohistochemistry - Rakesh Kumar Gupta; Ravindra Kumar Saran; Deepak Ghuliani; Lalit Garg; Abhijit Das (Indian Journal of Medical and Paediatric Oncology)
Malignant peripheral nerve sheath tumors (MPNSTs) are rare soft tissue tumors commonly arising from nerve roots in the extremities with a predilection in neurofibromatosis (NF) patients. MPNSTs are known to behave aggressively, with worse prognosis in nonresectable cases, and a 5-year survival of about 52% and 15% in resectable and unresectable cases, respectively. Although cytological diagnosis in a known case of NF-1 is possible, however, in the absence of any associated syndrome in a sporadic case, it is very challenging to accurately diagnose this tumor. Till date, to the best of our knowledge, only three cases of epithelioid MPNST correctly diagnosed on cytological examination have been described. We are presenting another case of epithelioid MPNST in a 40-year-old patient with stigmata of NF-1 since childhood, diagnosed on fine-needle aspiration cytology from the left flank mass with subsequent histopathology from left inguinal lymph node metastasis.